2020
DOI: 10.1016/j.heliyon.2020.e03412
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure self-care, factors influencing self-care and the relationship with health-related quality of life: A cross-sectional observational study

Abstract: Background: Self-care helps maintain health, prevents complications and improves the quality of life of patients living with heart failure (HF). Self-care is critical to HF management but has received limited attention in Nepal. Identification of the sociodemographic and clinical characteristics associated with self-care is crucial to tailoring appropriate self-care programs to improve health outcomes including patients' quality of life. Aims: The aims of this study were to describe self-care including the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
58
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 41 publications
6
58
1
8
Order By: Relevance
“…Good self-care is correlated to better quality of life. 13 It is hoped that the improvement in therapy adherence reduces the rehospitalization rate dan increased quality of life. [13][14][15] Based on study carried out on the…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Good self-care is correlated to better quality of life. 13 It is hoped that the improvement in therapy adherence reduces the rehospitalization rate dan increased quality of life. [13][14][15] Based on study carried out on the…”
Section: Introductionmentioning
confidence: 99%
“…Good self-care is correlated to better quality of life. 13 It is hoped that the improvement in therapy adherence reduces the rehospitalization rate dan increased quality of life. 13-15 Based on study carried out on the effect of self-management interventions on heart failure patients, the results showed that respondents in the intervention group experienced fewer hospitalizations and the quality of life of respondents in this group also increased for 12 months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embora o autocuidado adequado seja benéfico, a literatura aponta que a frequência de indivíduos com IC com autocuidado inadequado é elevada (Koirala et al 2020 ;Pape 2019;Flores 2019;Conceição et al 2015). Diversos fatores influenciam a capacidade para o autocuidado, como idade, sexo, QVRS, nível de escolaridade, sintomas depressivos, fração de ejeção ventricular (FEV) (Sedlar et al, 2017), déficits cognitivos (Uchmanowicz et al, 2017a), assim como também o conhecimento sobre a síndrome da IC e seu tratamento (Seid et al, 2019;Liu et al, 2014).…”
Section: Introductionunclassified
“…Tanto a IC como seu tratamento são complexos, necessitam de abordagem multidisciplinar especializada para que o paciente e seus familiares apresentem um adequado manejo do autocuidado (Montes-Muñoz et al, 2012). Diretrizes baseadas em evidências destacam a importância da implementação de programas de educação liderados por enfermeiros com foco na promoção de comportamentos de autocuidado para pacientes com IC (Koirala et al 2020;Rohde et al 2018;Baptiste et al 2016).…”
Section: Introductionunclassified